Connecting the Disconnected: Improving Education and Employment Outcomes Among Disadvantaged Youth - Peter B. Edelman; Harry J. Holzer (Institute for the Study of Labor (IZA), 2013)
In this paper we will briefly review recent trends in employment outcomes for disadvantaged youth, focusing specifically on those who have become disconnected from school and the labor market, and why these trends have occurred. We then review a range of policy prescriptions that might improve those outcomes. These policies include: 1) Efforts to enhance education and employment outcomes, both among in-school youth who are at risk of dropping out and becoming disconnected as well as out-of-school youth who have already done so; 2) Policies to increase earnings and incent more labor force participation among youth, such as expanding the eligibility of childless adults (and especially non-custodial parents) for the Earned Income Tax Credit (EITC); and 3) Specific policies to reduce barriers to employment faced by ex-offenders and non-custodial parents (NCPs). We also consider policies that target the demand side of the labor market, in efforts to spur the willingness of employers to hire these young people and perhaps to improve the quality of jobs available to them.
Keywords: J08; J13; 330; youth; education; employment; Jugendliche; Randgruppe; Arbeitsmarktpolitik; Bildungspolitik; Arbeitsmarktintegration; USA